1990
DOI: 10.1007/bf01798430
|View full text |Cite
|
Sign up to set email alerts
|

Variability of coronary flow reserve obtained immediately after coronary angioplasty

Abstract: Coronary flow reserve (CFR) improves in most patients immediately following coronary angioplasty (PTCA). The degree of improvement, however, may be variable and its predictive value for a favorable long-term angiographic result is unknown. To evaluate these issues, we used digital subtraction angiography to measure CFR in 15 patients before and immediately after PTCA. Minimum coronary diameter improved and percent diameter stenosis was reduced immediately following PTCA (from 0.75 +/- 0.35 mm to 2.19 +/- 0.56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown, that coronary flow reserve after PTCA is improved but in most patients not normalized [140,180,181,251]. Multiple explanations have been put forward in order to explain this surprising finding which has to be interpreted in view of angiographically optimal results on the one hand and the frequent CK elevation on the other hand.…”
Section: Mkroembofization Durÿ Coronary Interventionsmentioning
confidence: 99%
“…Multiple studies have shown, that coronary flow reserve after PTCA is improved but in most patients not normalized [140,180,181,251]. Multiple explanations have been put forward in order to explain this surprising finding which has to be interpreted in view of angiographically optimal results on the one hand and the frequent CK elevation on the other hand.…”
Section: Mkroembofization Durÿ Coronary Interventionsmentioning
confidence: 99%
“…Coronary flow reserve has been demonstrated to improve in most patients immediately following PTCA [15][16][17]. However, in another group of unselected patients, no significant improvement of the coronary flow reserve was noted [18].…”
Section: Discussionmentioning
confidence: 99%